Enzyme Responses to Phytoremediation of PAH-Contaminated Soil Using Echinacea purpurea (L.) - Rui Liu; Lixing Zhao; Caixia Jin; Nan Xiao; R. N. Jadeja; Ting Sun (Water, Air, & Soil Pollution, 2014)

Identification and validation of suitable reference genes for RT-qPCR analysis in mouse testis development - Zu-Kang Gong; Shuang-Jie Wang; Yong-Qi Huang; Rui-Qiang Zhao; Qi-Fang Zhu; Wen-Zhen Lin (Molecular Genetics and Genomics, 2014)

Upregulation of HIF-1α Via Activation of ERK and PI3K Pathway Mediated Protective Response to Microwave-Induced Mitochondrial Injury in Neuron-Like Cells - Li Zhao; Yue-Feng Yang; Ya-Bing Gao; Shui-Ming Wang; Li-Feng Wang; Hong-Yan Zuo; Ji Dong; Xin-Ping Xu; Zhen-Tao Su; Hong-Mei Zhou; Ling-Ling Zhu; Rui-Yun Peng (Molecular Neurobiology, 2014)

A down-regulated epi-allele of the genomes uncoupled 4 gene generates a xantha marker trait in rice - Rui-Qing Li; Jian-Zhong Huang; Hai-Jun Zhao; Hao-Wei Fu; You-Fa Li; Guo-Zhen Liu; Qing-Yao Shu (Theoretical and Applied Genetics, 2014)

Two new cadinane-type sesquiterpenes from the Chinese liverwort Frullania serrata - Rui-Juan Li; Rong-Xiu Zhu; Yu Zhao; Susan L. Morris-Natschke; Chin-Ho Chen; Song Wang; Jiao-Zhen Zhang; Jin-Chuan Zhou; Hong-Xiang Lou; Kuo-Hsiung Lee (Natural Product Research, 2014)

Production of low phytic acid rice by hairpin RNA- and artificial microRNA-mediated silencing of OsMIK in seeds - Wen-Xu Li; Jian-Zhong Huang; Hai-Jun Zhao; Yuan-Yuan Tan; Hai-Rui Cui; Yves Poirier; Qing-Yao Shu (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Transcription of the Human Sodium Channel SCN1A Gene Is Repressed by a Scaffolding Protein RACK1 - Zhao-Fei Dong; Ling-Jia Tang; Guang-Fei Deng; Tao Zeng; Shu-Jing Liu; Rui-Ping Wan; Ting Liu; Qi-Hua Zhao; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Molecular Neurobiology, 2014)

Cassiterite LA-MC-ICP-MS U/Pb and muscovite 40Ar/39Ar dating of tin deposits in the Tengchong-Lianghe tin district, NW Yunnan, China - Xiao-Cui Chen; Rui-Zhong Hu; Xian-Wu Bi; Hui-Min Li; Jiang-Bo Lan; Cheng-Hai Zhao; Jing-Jing Zhu (Mineralium Deposita, 2014)

Needle-free injection of insulin powder: delivery efficiency and skin irritation assessment - Chun-yu Li; Zhe-wei Wang; Can Tu; Jia-bo Wang; Bing-qian Jiang; Qi Li; Ling-na Zeng; Zhi-jie Ma; Ping Zhang; Yan-ling Zhao; Ya-ming Zhang; Dan Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Distance effect of matrix attachment regions on transgene expression in stably transfected Chinese hamster ovary cells - Jun-He Zhang; Xiao-Yin Wang; Tian-Yun Wang; Fang Wang; Wei-Hua Dong; Li Wang; Chun-Peng Zhao; Shu-Jie Chai; Rui Yang; Qin Li (Biotechnology Letters, 2014)

Zircon U–Pb geochronology and geochemistry of the Maoliger quartz monzodiorites, Inner Mongolia, China: implications for Carboniferous arc magmatism and closure of the Palaeo-Asian Ocean - Li-Min Wang; Xiao-Guo Chi; Zhi Zhao; Wei Sun; Rui Zhang; Shi-Yu Pan; Jing-Yu Quan (International Geology Review, 2014)

Toxic effects of sodium fluoride on cell proliferation and apoptosis of Leydig cells from young mice - Guo hua Song; Rui Li Wang; Zhao Yang Chen; Bin Zhang; Hai Long Wang; Mao Lin Liu; Ji Ping Gao; Xiao Yan Yan (Journal of Physiology and Biochemistry, 2014)

Soluble biglycan induces the production of ICAM-1 and MCP-1 in human aortic valve interstitial cells through TLR2/4 and the ERK1/2 pathway - Rui Song; Lihua Ao; Ke-seng Zhao; Daniel Zheng; Neil Venardos; David A. Fullerton; Xianzhong Meng (Inflammation Research, 2014)

Simultaneous Determination of Calycosin-7-O-β-d-Glucoside, Ononin, Calycosin, Formononetin, Astragaloside IV, and Astragaloside II in Rat Plasma After Oral Administration of Radix Astragali Extraction for Their Pharmacokinetic Studies by Ultra-Pressure Liquid Chromatography with Tandem Mass Spectrometry - Xiao-hua Liu; Jian-bang Zhao; Long Guo; Ying-lai Yang; Fang Hu; Rui-juan Zhu; Shi-lan Feng (Cell Biochemistry and Biophysics, 2014)

Isolation and characterization of nineteen novel polymorphic microsatellite loci for the northern snakehead Channa argus - Ruo-Jin Yan; Kai-Jian Wei; Xiang-Zhao Guo; Gui-Rong Zhang; Jonathan P. A. Gardner; Rui-Bin Yang; Kun-Ci Chen (Conservation Genetics Resources, 2014)

Bernoulli-based random undersampling schemes for 2D seismic data regularization - Rui Cai; Qun Zhao; De-Ping She; Li Yang; Hui Cao; Qin-Yong Yang (Applied Geophysics, 2014)

Erratum to: The Role of Autophagy Dysregulation in Manganese-Induced Dopaminergic Neurodegeneration - Jianbin Zhang; Rui Cao; Tongjian Cai; Michael Aschner; Fang Zhao; Ting Yao; Yaoming Chen; Zipeng Cao; Wenjing Luo; Jingyuan Chen (Neurotoxicity Research, 2014)

Seed-specific silencing of OsMRP5 reduces seed phytic acid and weight in rice - Wen-Xu Li; Hai-Jun Zhao; Wei-Qin Pang; Hai-Rui Cui; Yves Poirier; Qing-Yao Shu (Transgenic Research, 2014)

RETRACTED ARTICLE: Uncovering the pathogenesis and identifying novel targets of pancreatic cancer using bioinformatics approach - Li-Li Zhao; Tong Zhang; Li-Wei Zhuang; Bing-Zhu Yan; Rui-Feng Wang; Bing-Rong Liu (Molecular Biology Reports, 2014)

Characterization and expression profiles of MaACS and MaACO genes from mulberry (Morus alba L.) - Chang-ying Liu; Rui-hua Lü; Jun Li; Ai-chun Zhao; Xi-ling Wang; Umuhoza Diane; Xiao-hong Wang; Chuan-hong Wang; Ya-sheng Yu; Shu-mei Han; Cheng Lu; Mao-de Yu (Journal of Zhejiang University-SCIENCE B, 2014)

Airborne fine particulate matter induces multiple cell death pathways in human lung epithelial cells - Xiaobei Deng; Fang Zhang; Lijuan Wang; Wei Rui; Fang Long; Yong Zhao; Deliang Chen; Wenjun Ding (Apoptosis, 2014)

Identification of a putative cognate sensor kinase for the two‐component response regulator HrpG , a key regulator controlling the expression of the hrp genes in X anthomonas campestris pv. campestris - Rui‐Fang Li; Guang‐Tao Lu; Lei Li; Hui‐Zhao Su; Guo‐fang Feng; Ya Chen; Yong‐Qiang He; Bo‐Le Jiang; Dong‐Jie Tang; Ji‐Liang Tang (Environmental Microbiology, 2014)
Summary The bacterial phytopathogen X anthomonas campestris pv. campestris ( Xcc ) relies on the hrp (hypersensitive response and pathogenicity) genes to cause disease and induce hypersensitive response ( HR ). The hrp genes of bacterial phytopathogens are divided into two groups. Xcc hrp genes belong to group II . It has long been known that the group II hrp genes are activated by an AraC ‐type transcriptional regulator whose expression is controlled by a two‐component system ( TCS ) response regulator (named HrpG in Xcc ). However, no cognate sensor kinase has yet been identified. Here, we present evidence showing that the Xcc open‐reading frame XC _3670 encodes a TCS sensor kinase (named HpaS ). Mutation of hpaS almost completely abolished the HR induction and virulence. Bacterial two‐hybrid and protein pull‐down assays revealed that HpaS physically interacted with HrpG . Phos‐tag™ SDS‐PAGE analysis showed that mutation in hpaS reduced markedly the phosphorylation of HrpG in vivo . These data suggest that HpaS and HrpG are most likely to form a TCS . We also showed that XC _3669 (named hpaR2 ), which is adjacent to hpaS and encodes a putative TCS response regulator, is required for full virulence but not HR induction. HpaR2 also physically interacted with HpaS , suggesting that HpaS may also form another TCS with HpaR2 .

The effect of NF-κB antisense oligonucleotide on transdifferentiation of fibroblast in lung tissue of mice injured by bleomycin - Yan Zhou; Xiaoye Zhang; Mingqi Tan; Rui Zheng; Li Zhao (Molecular Biology Reports, 2014)

A novel variant in the 3′ UTR of human SCN1A gene from a patient with Dravet syndrome decreases mRNA stability mediated by GAPDH’s binding - Tao Zeng; Zhao-Fei Dong; Shu-Jing Liu; Rui-Ping Wan; Ling-Jia Tang; Ting Liu; Qi-Hua Zhao; Yi-Wu Shi; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Human Genetics, 2014)

Anti-stress properties and two HSP70s mRNA expressions of blunt snout bream (Megalobrama amblycephala) fed with all-plant-based diet - Wei Deng; Yuhua Zhao; Weimin Wang; Yasmeen Gul; Junming Cao; Yanhua Huang; Guangcheng Sheng; Zhujin Ding; Rui Du (Fish Physiology and Biochemistry, 2014)

Isolation and characterization of twenty-three polymorphic microsatellite loci in Schizothorax macropogon - Xiang-Zhao Guo; Gui-Rong Zhang; Ruo-Jin Yan; Wei Ji; Rui-Bin Yang; Kai-Jian Wei; Deng-Qiang Wang (Conservation Genetics Resources, 2014)

Development and characterization of 20 polymorphic microsatellite loci for the Lhasa schizothoracin Schizothorax waltoni - Xiang-Zhao Guo; Gui-Rong Zhang; Kai-Jian Wei; Wei Ji; Rui-Bin Yang; Jonathan P. A. Gardner; Qi-Wei Wei (Conservation Genetics Resources, 2014)

An automatic seismic signal detection method based on fourth-order statistics and applications - Xi-Qiang Liu; Yin Cai; Rui Zhao; Yin-Gang Zhao; Bao-An Qu; Zhi-Jun Feng; Hong Li (Applied Geophysics, 2014)

Expression and roles of As-NUPR1 protein from Artemia sinica during embryo development and in response to salinity stress - Rui Zhang; Feng Yao; Cheng Cheng; Yifei Chen; Ying Lv; Zengrong Li; Na Zhao; Ting Wang; Wenting Xin; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

Time-dependent damage constitutive model for the marble in the Jinping II hydropower station in China - Bing-Rui Chen; Xiao-Jun Zhao; Xia-Ting Feng; Hong-Bo Zhao; Shan-Yong Wang (Bulletin of Engineering Geology and the Environment, 2014)

Detection of respiratory syncytial virus fusion protein variants between 2009 and 2012 in China - Qiuling Xia; Lili Zhou; Caijing Peng; Rui Hao; Ke Ni; Na Zang; Luo Ren; Yu Deng; Xiaohong Xie; Linli He; Daiyin Tian; Lijia Wang; et al. (Archives of Virology, 2014)

Zircon geochronology constraints on the age and nature of ‘Precambrian metamorphic rocks’ in the Xing’an block of Northeast China - Wei Sun; Xiao-Guo Chi; Zhi Zhao; Shi-Yu Pan; Jian-Feng Liu; Rui Zhang; Jing-Yu Quan (International Geology Review, 2014)

Origin of the Miocene porphyries and their mafic microgranular enclaves from Dabu porphyry Cu–Mo deposit, southern Tibet: implications for magma mixing/mingling and mineralization - Song Wu; You-Ye Zheng; Xiang Sun; Sheng-Ao Liu; Rui-Rui Geng; Zhi-Ming You; Hai-Tao Ouyang; Dong Lei; Zhong-Ying Zhao (International Geology Review, 2014)

The Neuroprotective Effects of Isoflurane Preconditioning in a Murine Transient Global Cerebral Ischemia–Reperfusion Model: The Role of the Notch Signaling Pathway - Hao-peng Zhang; Yan-yan Sun; Xiao-mei Chen; Li-bang Yuan; Bin-xiao Su; Rui Ma; Rui-ni Zhao; Hai-long Dong; Lize Xiong (NeuroMolecular Medicine, 2014)

Isolation, culture, and characterization of primordial germ cells in Mongolian sheep - Chun Xia Liu; Wen Long Wang; Rui Yuan Zhao; Hai Tao Wang; Yi Yi Liu; Shen Yuan Wang; Huan Min Zhou (In Vitro Cellular & Developmental Biology - Animal, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

MicroRNA-128 regulates the differentiation of rat bone mesenchymal stem cells into neuron-like cells by Wnt signaling - Rui Wu; Yue Tang; Wenqiao Zang; Yuanyuan Wang; Min Li; Yuwen Du; Guoqiang Zhao; Yuming Xu (Molecular and Cellular Biochemistry, 2014)

Simazine biodegradation and community structures of ammonia-oxidizing microorganisms in bioaugmented soil: impact of ammonia and nitrate nitrogen sources - Rui Wan; Yuyin Yang; Weimin Sun; Zhao Wang; Shuguang Xie (Environmental Science and Pollution Research, 2014)

Cloning and expression patterns of the brine shrimp (Artemia sinica) glycogen phosphorylase (GPase) gene during development and in response to temperature stress - Na Zhao; Ming Hou; Ting Wang; Yifei Chen; Ying Lv; Zengrong Li; Rui Zhang; Wenting Xin; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

Effects of submerged macrophytes on the abundance and community composition of ammonia-oxidizing prokaryotes in a eutrophic lake - Da-yong Zhao; Juan Luo; Jin Zeng; Meng Wang; Wen-ming Yan; Rui Huang; Qinglong L. Wu (Environmental Science and Pollution Research, 2014)